Vein pattern verification and identification based on local geometric invariants constructed from minutia points and augmented with barcoded local feature - Pititheeraphab, Yutthana; Thongpance, Nuntachai; Aoyama, Hisayuki; Pintavirooj, Chuchart (My University, 2020)
This paper presents the development of a hybrid feature-dorsal hand vein and dorsal geometry-modality for human recognition. Our proposed hybrid feature extraction method exploits two types of features: dorsal hand geometric-related and local vein pattern. Using geometric affine invariants, the peg-free system extracts minutia points and vein termination and bifurcation and constructs a set of geometric invariants, which are then used to establish the correspondence between two sets of minutiae-one for the query vein image and the other for the reference vein image. When the correspondence is established, geometric transformation parameters are computed to align the query with the reference image. Once aligned, hybrid features are extracted for identification. In this study, the algorithm was tested on a database of 140 subjects, in which ten different dorsal hand geometric-related images were taken for each individual, and yielded the promising results. In this regard, we have achieved an equal error rate (EER) of 0.243%, indicating that our method is feasible and effective for dorsal vein recognition with high accuracy. This hierarchical scheme significantly improves the performance of personal verification and/or identification.
Keywords: Affine invariant; Biometric; Contactless; Dorsal hand vein recognition; Hybrid feature; Identification; Non-contact; Vein pattern; Verification